Transformation of university strategies in the digitalization of the educational space - Zhashkenova, R.B.; Aimagambetov, Ye.B.; Pritvorova, T.P.; Omarova, A.T.; Nakipova, G.Ye. (KU publ., 2020)
Object: is to analyze the strategy of universities in the context of the digital economy, where the emphasis is on transforming the strategy of universities in the field of their interaction with the state and the business community in the context of digitalization. Methods: research methodology is a set of methods, mechanisms, principles, measures to improve the efficiency of development and use of new information and communication technologies, which are a prerequisite for the further development of education and digital pedagogy, in the implementation of an effective information educational environment, which is the basis for the development of any university. Findings: authors for such indicators as the cost of services rendered and goods sold, produced on their own by the universities of the Republic of Kazakhstan and the internal costs of R&D in the Republic of Kazakhstan, hypothesized that there is a connection between: the total costs of ICT and the cost of services provided by the universities of the Republic of Kazakhstan ; ICT expenditures and scientific R&D expenditures in the Republic of Kazakhstan. Conclusions: based on the conducted regression analysis, the author of the article concluded that: 1) with an increase in internal R&D costs by 1% of its average level, the total costs of ICT will increase by 1.342% of their average level, with the cost of services rendered and goods sold by themselves produced by the universities of the Republic of Kazakhstan unchanged; 2) with an increase in the cost of services rendered and goods sold, produced on their own, by the universities of the Republic of Kazakhstan by 1% of their average level, the total cost of ICT will increase by 0.025% of its average level, while the volume of internal R&D costs remains unchanged.
Университеттер стратегияларын білім беру кеңістігін сандықтандыру жағдайында трансформациялау
Трансформация стратегии университетов в условиях цифровизации образовательного пространства
Keywords: digitalization; business community; strategy; education system; innovation; innovativeness; competitiveness; educational process; management; quality; educational space